Lithium battery and its manufacturing method

By adopting an alternating stacking structure and an intermediate layer in the electrode combination film of the lithium battery, and manufacturing the second positive electrode using a dry mixing and dry winding process, the problem of defects in the outer electrode combination film during the lithium battery manufacturing process is solved, and the energy density and cycling stability of the lithium battery are improved.

JP7657862B2Active Publication Date: 2025-04-07SAMSUNG SDI CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023118467
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-20
Publication Date
2025-04-07
Estimated Expiration
2043-07-20

AI Technical Summary

Technical Problem

In the manufacturing process of existing lithium batteries, defects in the outer electrode combination film are prone to occur, resulting in insufficient energy density and stability of lithium batteries.

Method used

A structure in which multiple layers of positive and negative electrodes are alternately stacked in the electrode combination film, wherein the second positive electrode is added to the outer layer and the intermediate layer is added to reduce the thickness and surface roughness of the second positive electrode, and the second positive electrode is fabricated by a dry mixing and dry winding process.

Benefits of technology

It effectively suppresses deformation and defects of the electrode combination film during the manufacturing process, and improves the energy density and cycle stability of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657862000006
    Figure 0007657862000006
  • Figure 0007657862000007
    Figure 0007657862000007
  • Figure 0007657862000008
    Figure 0007657862000008
Patent Text Reader

Abstract

To provide a lithium battery and a manufacturing method for the same.SOLUTION: A lithium battery includes an electrode group stack in which a plurality of positive electrodes and one or more negative electrodes are alternately stacked in a thickness direction. The plurality of positive electrodes include a first positive electrode 400 and a second positive electrode 401. The first positive electrode is an inner layer of the electrode group stack. The second positive electrode is an outermost layer of the electrode group stack. The first positive electrode includes a first positive electrode current collector 200 and a first positive electrode active material layer 100. The first positive electrode active material layer is disposed on both surfaces of the first positive electrode current collector. The second electrode includes a second positive electrode current collector 201, a second positive electrode active material layer 101, and an intermediate layer 301 disposed between the second positive electrode current collector and the second positive electrode active material layer. The second positive electrode current collector includes a first surface and a second surface. The first surface faces the inner layer and the second surface is an opposite surface of the first surface. The second positive electrode active material layer is disposed on the first surface and is not disposed on the second surface. A thickness of the second positive electrode current collector is equal to or smaller than a thickness of the first positive electrode current collector. An electrode manufacturing method is also provided.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium battery and a method for manufacturing the same. [Background technology]

[0002] In order to meet the trend of miniaturization and high performance of various devices, it is becoming important for lithium batteries to have high energy density in addition to miniaturization and weight reduction, i.e., high-capacity lithium batteries are becoming important.

[0003] To implement lithium batteries suitable for these applications, electrode stacks having high loadings are used.

[0004] During the manufacturing process of the laminate, defects are likely to occur in the electrodes arranged in the outermost layers of the electrode group laminate, which in turn results in defects in lithium batteries including such laminates.

[0005] There is a need for a lithium battery in which the formation of defects during the manufacturing process of such laminates is suppressed. Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a lithium battery in which the generation of defects is suppressed during the manufacturing process of an electrode group laminate and the energy density is improved.

[0007] Another problem to be solved by the present invention is to provide a method for manufacturing the lithium battery. [Means for solving the problem]

[0008] According to one aspect, the present invention includes an electrode group stack in which a plurality of positive electrodes and one or more negative electrodes are alternately stacked in a thickness direction, the plurality of positive electrodes include a first positive electrode and a second positive electrode, the first positive electrode being an inner layer of the electrode group stack, and the second positive electrode being an outermost layer of the electrode group stack. the first positive electrode current collector includes a first positive electrode current collector and a first positive electrode active material layer, the first positive electrode active material layer being disposed on both sides of the first positive electrode current collector; the second positive electrode current collector includes a second positive electrode current collector, a second positive electrode active material layer, and an interlayer disposed between the second positive electrode current collector and the second positive electrode active material layer, the second positive electrode current collector includes a first surface and a second surface, the first surface facing the inner layer and the second surface being an opposite surface to the first surface, the second positive electrode active material layer being disposed on the first surface and not on the second surface, and a thickness of the second positive electrode current collector is equal to or smaller than a thickness of the first positive electrode current collector.

[0009] According to another aspect, the present invention provides an electrode group stack in which a plurality of negative electrodes and one or more positive electrodes are alternately stacked in a thickness direction, the plurality of negative electrodes including a first negative electrode and a second negative electrode, the first negative electrode being an inner layer of the electrode group stack, and the second negative electrode being an outermost layer of the electrode group stack. the first negative electrode current collector includes a first negative electrode current collector and a first negative electrode active material layer, the first negative electrode active material layer being disposed on both sides of the first negative electrode current collector; the second negative electrode current collector includes a second negative electrode current collector and a second negative electrode active material layer, and an interlayer disposed between the second negative electrode current collector and the second negative electrode active material layer, the second negative electrode current collector includes a first surface and a second surface, the first surface facing the inner layer and the second surface being an opposite surface to the first surface, the second negative electrode active material layer being disposed on the first surface and not on the second surface, and a thickness of the second negative electrode current collector is equal to or smaller than a thickness of the first negative electrode current collector.

[0010] According to yet another aspect, a lithium battery includes the steps of: dry-mixing a second positive electrode active material, a dry conductive material, and a dry binder to prepare a dry mixture; providing a second positive electrode current collector; disposing an intermediate layer on one surface of the second positive electrode current collector; and disposing the dry mixture on the intermediate layer and rolling it to manufacture a second positive electrode in which a second positive electrode active material layer is disposed on one surface of the second positive electrode current collector, the lithium battery including an electrode group stack in which a plurality of positive electrodes and one or more negative electrodes are alternately stacked in a thickness direction, the plurality of positive electrodes including a first positive electrode and a second positive electrode, the first positive electrode being an inner layer of the electrode group stack, the second positive electrode being an outermost layer of the electrode group stack, the first positive electrode current collector includes a first positive electrode current collector and a first positive electrode active material layer, the first positive electrode active material layer being disposed on both sides of the first positive electrode current collector; the second positive electrode current collector includes a second positive electrode current collector and a second positive electrode active material layer, and an interlayer disposed between the second positive electrode current collector and the second positive electrode active material layer, the second positive electrode current collector includes a first surface and a second surface, the first surface facing the inner layer and the second surface being an opposite surface to the first surface, the second positive electrode active material layer being disposed on the first surface and not on the second surface, and a thickness of the second positive electrode current collector is equal to or smaller than a thickness of the first positive electrode current collector. Effect of the Invention

[0011] According to one aspect, since the generation of defects is suppressed during the manufacturing process of the electrode group stack, defects in a lithium battery including the electrode group stack are suppressed. [Brief description of the drawings]

[0012] [Figure 1] 1 is a schematic diagram of an electrode group assembly according to an illustrative embodiment; [Diagram 2] 1 is an image of a second positive electrode prepared in Example 1. [Diagram 3] 1 is an image of a second positive electrode prepared in Comparative Example 1. [Figure 4]1 is a schematic diagram of a lithium battery according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present inventive concept described below can be modified in various ways and can have various embodiments, and specific embodiments are illustrated in the drawings and described in detail in the detailed description. However, this is not intended to limit the present inventive concept to a specific embodiment, and it should be understood that the present inventive concept includes any modifications, equivalents, or alternatives that fall within the technical scope of the present inventive concept.

[0014] The terms used below are merely used to describe specific embodiments and are not intended to limit the present invention. Singular expressions include plural expressions unless the context clearly indicates otherwise. In the following, terms such as "include" or "have" indicate the presence of a feature, number, step, operation, component, part, ingredient, material, or combination thereof described in the specification, and should be understood not to preclude the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, ingredients, materials, or combinations thereof. In the following, " / " can be interpreted as "and" or "or" depending on the situation.

[0015] In the drawings, thicknesses are exaggerated or reduced to clearly depict multiple layers and regions. Similar parts are designated by the same reference numerals throughout the specification. Throughout the specification, when a part such as a layer, film, region, plate, etc. is described as being "on" or "above" another part, this does not only mean that it is directly on top of the other part, but also includes cases where there is another part in between. Throughout the specification, terms such as first, second, etc. may be used to describe various components, but the components should not be limited by the terms. Terms are used only to distinguish one component from another.

[0016] As used herein, "dry" or "dry type" refers to a state in which a material is not intentionally in contact with a solvent such as a process solvent or a state in which a solvent is not intentionally included. For example, a dry electrode active material refers to an electrode active material that is not intentionally in contact with a solvent or an electrode active material that is not intentionally included with a solvent. For example, a dry conductive material refers to a conductive material that is not intentionally in contact with a solvent or a conductive material that is not intentionally included with a solvent. For example, a dry binder refers to a binder that is not intentionally in contact with a solvent or a binder that is not intentionally included with a solvent. For example, a binder that is not mixed with a solvent and is in a liquid state at room temperature is a dry binder.

[0017] Hereinafter, an electrode according to an example embodiment, a lithium battery including the same, and a method for manufacturing the same will be described in more detail.

[0018] The lithium battery according to an embodiment includes an electrode group stack in which a plurality of positive electrodes and one or more negative electrodes are alternately stacked in a thickness direction, the plurality of positive electrodes include a first positive electrode and a second positive electrode, the first positive electrode being an inner layer of the electrode group stack, and the second positive electrode being an outermost layer of the electrode group stack. the first positive electrode current collector includes a first positive electrode current collector and a first positive electrode active material layer, the first positive electrode active material layer being disposed on both sides of the first positive electrode current collector; the second positive electrode current collector includes a second positive electrode current collector, a second positive electrode active material layer, and an interlayer disposed between the second positive electrode current collector and the second positive electrode active material layer, the second positive electrode current collector includes a first surface and a second surface, the first surface facing the inner layer and the second surface being an opposite surface to the first surface, the second positive electrode active material layer being disposed on the first surface and not on the second surface, and a thickness of the second positive electrode current collector is equal to or smaller than a thickness of the first positive electrode current collector.

[0019] In the lithium battery of the present disclosure, the second positive electrode disposed in the outermost layer of the electrode group laminate includes an intermediate layer between the second positive electrode collector and the second positive electrode active material layer, thereby suppressing warping of the second positive electrode. Therefore, the occurrence of defects such as curling and bending of the second positive electrode is suppressed during the manufacturing process of the electrode group laminate. In addition, the second positive electrode is a single-sided electrode, and the energy density of the lithium battery including the electrode group laminate is improved. In addition, the thickness of the second positive electrode collector disposed in the second positive electrode is the same as the thickness of the first positive electrode collector disposed in the first positive electrode, or the thickness of the second positive electrode collector disposed in the second positive electrode is thinner than the thickness of the first positive electrode collector disposed in the first positive electrode, thereby improving the energy density of the lithium battery. In addition, the occurrence of defects during the manufacturing process of the electrode group laminate is suppressed. Since the intermediate layer provides a bonding force between the second positive electrode current collector and the second positive electrode active material layer, the pressure required to bond the second positive electrode current collector and the second positive electrode active material layer during the manufacture of the second positive electrode is reduced, thereby suppressing warping of the second positive electrode.

[0020] In contrast, if a single-sided electrode is disposed on the outermost layer of an electrode group laminate in a conventional lithium battery, the single-sided electrode is likely to be warped into a cylindrical shape by rolling during the manufacturing process of the single-sided electrode. Therefore, it is difficult to match the position of the single-sided electrode disposed on the upper or lower end of the electrode group laminate with the electrode group laminate, and defects such as curling and bending are likely to occur in the single-sided electrode during the manufacturing process. In addition, if a double-sided electrode is disposed on the outermost layer of the electrode group laminate, only one side of the electrode facing the exterior body of the positive electrode participates in the electrode reaction, and the other side does not participate in the electrode reaction, which is inefficient. In addition, the energy density of a lithium battery including such an electrode group laminate is reduced.

[0021] In the lithium battery of the present disclosure, the ratio of the thickness of the first positive electrode current collector to the thickness of the second positive electrode current collector is, for example, 1:0.2 to 1:1, 1:0.3 to 1:1, 1:0.4 to 1:1, 1:0.5 to 1:1, 1:0.6 to 1:1, 1:0.7 to 1:1, 1:0.8 to 1:1, or 1:0.9 to 1:1. When the ratio of the thickness of the first positive electrode current collector to the thickness of the second positive electrode current collector falls within such a range, the energy density of the lithium battery can be further improved.

[0022] The thickness of the second positive electrode current collector is, for example, less than 15 μm, 14.5 μm or less, 14 μm or less, 13 μm or less, or 12 μm or less. The thickness of the second positive electrode current collector is, for example, 0.1 μm to less than 15 μm, 1 μm to 14.5 μm, 2 μm to 14 μm, 3 μm to 14 μm, 5 μm to 14 μm, 7 μm to 13 μm, or 10 μm to 12 μm. The thickness of the first positive electrode current collector is, for example, 15 μm or more, 20 μm or more, or 30 μm or more. The thickness of the first positive electrode current collector is, for example, 15 μm to 100 μm, 15 μm to 50 μm, 15 μm to 30 μm, or 15 μm to 20 μm.

[0023] The second positive electrode current collector has a reduced surface roughness compared to the first positive electrode current collector included in the first positive electrode. The reduced surface roughness of the second positive electrode current collector surface allows the second positive electrode current collector to form a uniform interface with the second positive electrode active material layer and / or the intermediate layer. As a result, local side reactions and / or non-uniform electrode reactions at the interface between the second positive electrode current collector and a different layer are suppressed, and the cycle characteristics of a lithium battery including such an electrode may be improved.

[0024] Maximum Roughness Depth, R max ) is, for example, larger than the maximum roughness of the second positive electrode current collector surface. That is, the maximum roughness (R max ) is smaller than the maximum roughness of the first positive electrode current collector surface. a) is, for example, larger than the average roughness of the second positive electrode current collector surface. That is, the average roughness (R a ) is smaller than the average roughness of the first positive electrode current collector surface, for example. The root mean square (RMS) roughness, Rq, of the first positive electrode current collector surface is larger than the root mean square roughness of the second positive electrode current collector surface. The root mean square (RMS) roughness, Rq, of the second positive electrode current collector surface is smaller than the average roughness of the first positive electrode current collector surface, for example. q ) is also smaller than the root mean square roughness of the surface of the first positive electrode current collector.

[0025] Maximum Roughness Depth, R max ) is, for example, 3 μm or less, 2 μm or less, 1 μm or less, 0.5 μm or less, or 0.1 μm or less. max ) may be, for example, 10 nm to 3 μm, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 0.5 μm, or 10 nm to 0.1 μm.

[0026] The mean roughness (R a ) is, for example, 2 μm or less, 1 μm or less, 0.5 μm or less, or 0.1 μm or less. a ) may be, for example, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 0.5 μm, or 10 nm to 0.1 μm.

[0027] The root mean square (RMS) roughness, R q ) is, for example, 2 μm or less, 1 μm or less, 0.5 μm or less, or 0.1 μm or less. q ) may be, for example, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 0.5 μm, or 10 nm to 0.1 μm.

[0028] The material constituting the second positive electrode current collector is a material that does not react with lithium, i.e., does not form an alloy or compound with lithium, and is conductive, and any of these can be used. The second positive electrode current collector is, for example, a metal or an alloy. The second positive electrode current collector can be made of, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The second positive electrode current collector can have a form selected from, for example, a sheet, a foil, a film, a plate, a porous body, a mesoporous body, a through-hole-containing body, a polygonal ring body, a mesh body, a foam body, and a nonwoven fabric body, but is not necessarily limited to such a form, and any form used in the technical field can be used.

[0029] The interlayer may include, for example, a binder. When the interlayer includes a binder, the binding force between the second positive electrode current collector and the second positive electrode active material layer may be further improved. The binder included in the interlayer may be, for example, a conductive binder or a non-conductive binder. The conductive binder may be, for example, an ion conductive binder and / or an electronic conductive binder. A binder having both ion conductivity and electronic conductivity may also be classified as an ion conductive binder or an electronic conductive binder. Examples of the ion conductive binder include polystyrene sulfonate (PSS), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), poly(methylmethacrylate) (PMMA), polyethylene oxide (PEO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), polyethylenedioxythiophene (PEDOT), polypyrrole (PPY), polyacrylonitrile (PAN), polyaniline, and polyacetylene. The ion conductive binder may include a polar functional group.Examples of ion-conductive binders containing polar functional groups include Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, sulfonated poly(ether ether ketone), SPEEK, sulfonated poly(arylene ether ketone ketone sulfone), SPAEKKS, sulfonated poly(aryl ether ketone), SPAEK, poly[bis(benzimidazobenzisoquinolinones)], SPBIBI, poly(styrene sulfonate), PSS), lithium 9,10-diphenylanthracene-2-sulfonate (DPASLi). + ) and the like. Examples of the electronically conductive binder include polyacetylene, polythiophene, polypyrrole, poly(p-phenylene), poly(phenylenevinylene), poly(phenylenesulfide), and polyaniline. The intermediate layer is also, for example, a conductive layer containing a conductive polymer. The binder contained in the intermediate layer can be selected from, for example, the binders contained in the electrode active material layer. The intermediate layer can contain, for example, the same binder as that in the electrode active material layer. The binder contained in the intermediate layer is, for example, a fluorine-based binder. The fluorine-based binder contained in the intermediate layer is, for example, polyvinylidene fluoride (PVDF). The intermediate layer is, for example, disposed on the electrode current collector in a dry or wet manner. The intermediate layer may also be, for example, a bonding layer that includes a binder.

[0030] The intermediate layer may include, for example, a carbon-based conductive material. The carbon-based conductive material included in the intermediate layer may be selected from the carbon-based conductive materials included in the electrode active material layer. The intermediate layer may include the same carbon-based conductive material as the electrode active material layer. Since the intermediate layer includes a carbon-based conductive material, the intermediate layer is also, for example, a conductive layer. The intermediate layer is also, for example, a conductive binding layer including a binder and a carbon-based conductive material.

[0031] The intermediate layer may be disposed on the second positive electrode current collector in a dry manner, for example, by deposition, such as CVD, PVD, etc. The intermediate layer may be disposed on the second positive electrode current collector, for example, by depositing a carbon-based conductive material on the second positive electrode current collector by deposition. The intermediate layer manufactured by the dry method is made of a carbon-based conductive material and does not include a binder. The intermediate layer may be disposed on the second positive electrode current collector in a wet manner, for example, by spin coating, dip coating, etc. The intermediate layer may be disposed on the second positive electrode current collector, for example, by coating a composition including a carbon-based conductive material, a binder, and a solvent on the second positive electrode current collector and drying it. The intermediate layer includes a binder and does not include a carbon-based conductive material. The intermediate layer may be disposed on the second positive electrode current collector, for example, by coating a composition including a binder and a solvent on the second positive electrode current collector and drying it. Since the intermediate layer has a small thickness, even if an intermediate layer that does not contain a carbon-based conductive material is disposed between the second positive electrode current collector and the second positive electrode active material layer, the reversibility of the electrode reaction at the second positive electrode does not change substantially. The intermediate layer may have a single layer structure or a multilayer structure including multiple layers.

[0032] The interlayer may be disposed on one or both sides of the second positive electrode current collector. The interlayer may be disposed, for example, directly on one or both sides of the second positive electrode current collector. Therefore, no other layer is disposed between the second positive electrode current collector and the interlayer. By disposing the interlayer directly on one or both sides of the second positive electrode current collector, the binding strength between the second positive electrode current collector and the second positive electrode active material layer may be further improved. The thickness of the interlayer is, for example, 0.01% to 30% of the thickness of the second positive electrode current collector. The thickness of the intermediate layer is, for example, 0.01% to 30%, 0.1% to 30%, 0.5% to 30%, 1% to 30%, 0.5% to 25%, 0.5% to 20%, 0.5% to 15%, 0.5% to 10%, 0.5% to 5%, or 0.5% to 3% of the thickness of the second positive electrode current collector. The thickness of the intermediate layer is, for example, 10 nm to 5 μm, 50 nm to 5 μm, 200 nm to 4 μm, 500 nm to 3 μm, 500 nm to 2 μm, 500 nm to 1.5 μm, or 700 nm to 1.3 μm. When the intermediate layer has a thickness in such a range, the binding force between the second positive electrode current collector and the second positive electrode active material layer is further improved, and an increase in the interface resistance can be suppressed.

[0033] The second positive electrode active material layer may include, for example, a second positive electrode active material and a binder.

[0034] The second cathode active material included in the second cathode active material layer is, for example, a dry cathode active material. The dry cathode active material is, for example, a cathode active material that is impregnated, dissolved, or not dispersed in a process solvent. The dry cathode active material is, for example, a cathode active material that includes a process solvent or is not in contact with a process solvent. The binder included in the second cathode active material layer is, for example, a dry binder. The dry binder is, for example, a binder that is impregnated, dissolved, or not dispersed in a process solvent. The dry binder is, for example, a binder that includes a process solvent or is not in contact with a process solvent. The process solvent is a solvent used in the manufacturing process of the second cathode.

[0035] The dry binder may be, for example, a fibrillized binder. The fibrillized binder may act as a matrix that supports and binds the second positive electrode active material and other components contained in the second positive electrode active material layer. The fibrillized binder may be confirmed to have a fibrous form, for example, through a scanning electron microscope image of the cross section of the electrode. The fibrillized binder may have an aspect ratio of, for example, 10 or more, 20 or more, 50 or more, or 100 or more. The dry binder may be, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexapropylene (PVDF-HFP) copolymer, polyvinylidene fluoride (PVDF), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, cellulose, polyvinylpyrrolidone, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or a copolymer thereof, but is not necessarily limited thereto, and any binder used in the manufacture of dry electrodes may be used. The dry binder may particularly include a fluorine-based binder. The fluorine-based binder may be, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexapropylene (PVDF-HFP) copolymer, or polyvinylidene fluoride (PVDF). The content of the dry binder in the second positive electrode active material layer is, for example, 1 wt% to 10 wt%, or 1 wt% to 5 wt%, based on the total weight of the second positive electrode active material layer. When the second positive electrode active material layer contains the dry binder in such a range, the binding strength of the second positive electrode is improved, and the second positive electrode can maintain a high energy density.

[0036] The second positive electrode active material layer further includes, for example, a conductive material. The conductive material is, for example, a dry conductive material. The dry conductive material is, for example, a conductive material that is not impregnated, dissolved, or dispersed in a solvent. The dry conductive material is, for example, a conductive material that includes a solvent or does not contact a solvent. The dry conductive material is, for example, a carbon-based conductive material, a metal-based conductive material, or a combination thereof. The dry conductive material includes, for example, a carbon-based conductive material. The carbon-based conductive material includes, for example, a particulate conductive material. The particulate conductive material is, for example, carbon black, graphite fine particles, natural graphite, artificial graphite, acetylene black, Ketjen black, etc., but is not limited thereto, and any material used as a carbon-based particulate conductive material in the technical field can be used. The carbon-based conductive material includes, for example, a fibrous conductive material. The fibrous conductive material is, for example, carbon nanotubes, carbon fibers, etc., but is not limited thereto, and any material used as a fibrous conductive material in the technical field can be used. The content of the dry conductive material in the second positive electrode active material layer is, for example, 1 to 10 wt % or 1 to 5 wt % based on the total weight of the second positive electrode active material layer. When the second positive electrode active material layer contains the dry conductive material in such a range, the conductivity of the second positive electrode is improved, and the second positive electrode can maintain a high energy density.

[0037] The second positive electrode active material layer is, for example, a self-standing film. The second positive electrode active material layer can be, for example, a film without a support. Therefore, the second positive electrode active material layer can be provided as a separate self-standing film and then disposed on the second positive electrode current collector. The second positive electrode active material layer is manufactured by a dry process, and therefore does not contain any intentionally added process solvent. For example, it does not contain any residual processing solvent. Although a trace amount of solvent may remain unintentionally in the second positive electrode active material layer, such residual solvent is not an intentionally added process solvent. Therefore, the second positive electrode active material layer is distinguished from a wet positive electrode active material layer manufactured by mixing components with a process solvent and then removing part or all of the process solvent by drying.

[0038] The thickness of the second positive electrode active material layer is, for example, the same as or thicker than the thickness of the first positive electrode active material layer. The thickness of the second positive electrode active material layer disposed on the second positive electrode current collector is also the same as the thickness of the first positive electrode active material layer disposed on the second positive electrode current collector. The thickness of the second positive electrode active material layer disposed on the second positive electrode current collector is thicker than the thickness of the first positive electrode active material layer disposed on the first positive electrode current collector. Since the second positive electrode active material layer has a thickness equal to or greater than that of the first positive electrode active material layer, the generation of defects in the second positive electrode can be suppressed during the manufacturing process of the electrode group laminate. The ratio of the thickness of the first positive electrode active material layer to the thickness of the second positive electrode active material layer is, for example, 1:1 to 1:3, 1:1 to 1:2.5, 1:1 to 1:2, 1:1 to 1:1.5, 1:1 to 1:1.3, 1:1 to 1:1.2, or 1:1 to 1:1.1. When the ratio of the thickness of the first positive electrode active material layer to the thickness of the second positive electrode active material layer is within such a range, the generation of defects can be effectively suppressed during the manufacturing process of the electrode group assembly and the lithium battery including the same.

[0039] The mixture density of the second positive electrode active material layer is, for example, the same as or lower than the mixture density of the first positive electrode active material layer. The mixture density of the second positive electrode active material layer disposed on the second positive electrode current collector is the same as the mixture density of the first positive electrode active material layer disposed on the first positive electrode current collector, or the mixture density of the second positive electrode active material layer disposed on the second positive electrode current collector is lower than the mixture density of the first positive electrode active material layer disposed on the first positive electrode current collector. Since the second positive electrode active material layer has a mixture density equal to or lower than that of the first positive electrode active material layer, the generation of defects in the second positive electrode can be suppressed during the manufacturing process of the electrode group laminate. The ratio of the mixture density of the first positive electrode active material layer to the mixture density of the second positive electrode active material layer is, for example, 1:0.5 to 1:1, 1:0.6 to 1:1, 1:0.7 to 1:1, 1:0.8 to 1:1, or 1:0.9 to 1:1. When the ratio of the mix density of the first positive electrode active material layer to the mix density of the second positive electrode active material layer is within such a range, the generation of defects can be effectively suppressed during the manufacturing process of the electrode group assembly and the lithium battery including the same.

[0040] The mixture density of the second positive electrode active material layer is, for example, 1 g / cm 3 ~5g / cm3 , 2g / cm 3 ~5g / cm 3 , 3g / cm 3 ~5g / cm 3 , or 3g / cm 3 ~4g / cm 3 The mixture density of the second positive electrode active material layer can be determined by measuring the volume and weight of the second positive electrode active material layer included in the manufactured second positive electrode. When the second positive electrode active material layer has a mixture density in such a range, a lithium battery including the second positive electrode can provide improved energy density.

[0041] In the second positive electrode active material layer, when measured by SAICAS (surface and interfacial measuring analysis system), the vertical relative adhesive strength (F) was measured based on a depth from a first point 5% away from the surface of the second positive electrode active material layer in the direction of the second positive electrode current collector to a second point 5% away from the surface of the second positive electrode current collector with respect to the entire thickness of the second positive electrode active material layer. VR , Vertical Relative Force) is, for example, 300% or less. The vertical relative binding force change rate is, for example, 10 to 300%, 10 to 250%, 10 to 200%, 10 to 150%, or 10 to 100%. The second point 5% away from the surface of the second positive electrode current collector in the second positive electrode active material layer direction corresponds to, for example, a point 95% away from the surface of the second positive electrode active material layer in the second positive electrode current collector direction with respect to the entire thickness of the second positive electrode active material layer. The vertical relative binding force is calculated from the following Equation 1. For the SAICAS measurement method, see, for example, Evaluation Example 1.

[0042] [Formula 1] Vertical relative adhesive force (F V , Vertical Relative Force) change rate = [(Maximum value of vertical relative adhesive force (F VR1 )-Minimum value of vertical relative adhesive force (F VR2 )) / Minimum value of vertical relative adhesive force (F VR2 )] x 100

[0043] In the second positive electrode active material layer, the rate of change in the vertical relative binding strength is 300% or less when measured by SAICAS (surface and interfacial measuring analysis system), and the uniformity of the distribution of components in the second positive electrode can be improved. In addition, the reversibility of the electrode reaction can be improved because side reactions and increases in internal resistance due to non-uniform distribution of the components in the second positive electrode active material layer are suppressed. Even in the case of a second positive electrode with high loading, the cycle characteristics of the lithium battery can be improved.

[0044] In the second positive electrode active material layer, a first horizontal direction adhesive strength (F) at a first point 10% apart from the surface of the second positive electrode active material layer in the direction toward the second positive electrode current collector with respect to the entire depth from the surface of the second positive electrode active material layer to the surface of the second positive electrode current collector during the SAICAS measurement. H1 A second horizontal force (F , Horizontal Force) at a second point 10% apart from the surface of the second positive electrode current collector in the second positive electrode active material layer direction (e.g., in the depth direction) H2 The ratio of the horizontal adhesive force (Horizontal Force) is, for example, 50% or more. The ratio of the horizontal adhesive force is, for example, 50 to 100%, 60 to 100%, 70 to 100%, 80 to 100%, or 90 to 100%. The second point 10% apart from the surface of the second positive electrode current collector in the direction of the second positive electrode active material layer corresponds to, for example, a point 90% apart from the surface of the second positive electrode active material layer in the direction of the second positive electrode current collector with respect to the entire thickness of the second positive electrode active material layer. The ratio of the horizontal adhesive force is expressed, for example, by the following formula 2. For the SAICAS measurement method, see, for example, Evaluation Example 2.

[0045] [Formula 2] Horizontal adhesion ratio = [Second horizontal adhesion (F H2 ) / First horizontal adhesion force (F H1 )] x 100

[0046] When the horizontal adhesion ratio is 50% or more in the SAICAS measurement, the uniformity of the distribution of the components in the second positive electrode is further improved. When the second positive electrode has a horizontal adhesion ratio in this range, the cycle characteristics of a lithium battery using such a second positive electrode are further improved.

[0047] The above-mentioned first positive electrode active material layer and second positive electrode active material layer may contain a first positive electrode active material and a second positive electrode active material, respectively.

[0048] The first positive electrode active material and / or the second positive electrode active material may be, for example, a lithium metal oxide, and any material commonly used in the art may be used without limitation.

[0049] The first positive electrode active material and / or the second positive electrode active material may be, for example, one or more composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof. Specific examples thereof include Li a A 1-b B b D2 (wherein, 0.90≦a≦1 and 0≦b≦0.5); Li a E 1-b B b O 2-c D c (wherein, 0.90≦a≦1, 0≦b≦0.5, and 0≦c≦0.05); LiE 2-b B b O 4-c D c (wherein, 0≦b≦0.5 and 0≦c≦0.05); Li a Ni 1-b-c Co b B c D α (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Co b B c O 2-α F α (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Lia Ni 1-b-c Co b B c O 2-α F2 (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b B c D α (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Mn b B c O 2-α F α (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b B c O 2-α F2 (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni b E c G d O2 (wherein, 0.90≦a≦1, 0≦b≦0.9, 0≦c≦0.5, and 0.001≦d≦0.1); Li a Ni b Co c Mn d G e O2 (wherein, 0.90≦a≦1, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, and 0.001≦e≦0.1); Li a NiG b O2 (wherein, 0.90≦a≦1, 0.001≦b≦0.1); Li a CoG b O2 (wherein, 0.90≦a≦1, 0.001≦b≦0.1); Li a MnG b O2 (wherein, 0.90≦a≦1, 0.001≦b≦0.1); Li a Mn2G bO4 (wherein 0.90≦a≦1, 0.001≦b≦0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiIO2; LiNiVO4; Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f) A compound expressed by any one of the chemical formulas Fe2(PO4)3(0≦f≦2);LiFePO4 can be used.

[0050] In the chemical formula expressing the above-mentioned compound, A is Ni, Co, Mn, or a combination thereof, B is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements, or a combination thereof, D is O, F, S, P, or a combination thereof, E is Co, Mn, or a combination thereof, F is F, S, P, or a combination thereof, G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof, Q is Ti, Mo, Mn, or a combination thereof, I is Cr, V, Fe, Sc, Y, or a combination thereof, and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof. It is also possible to use a compound having a coating layer added to the surface of the above-mentioned compound, and it is also possible to use a mixture of the above-mentioned compound and a compound having a coating layer added thereto. The coating layer added to the surface of the above-mentioned compound includes, for example, a coating element compound such as an oxide, hydroxide, oxyhydroxide, oxycarbonate, or hydroxycarbonate of the coating element of the coating element. The compound forming such a coating layer is amorphous or crystalline. The coating element contained in the coating layer is Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The method of forming the coating layer is selected within a range that does not adversely affect the physical properties of the positive electrode active material. The coating method is, for example, spray coating, immersion, etc. The specific coating method is well understood by those skilled in the art, so a detailed description will be omitted.

[0051] The content of the first positive electrode active material included in the first positive electrode active material layer is, for example, 80 to 98 wt%, or 90 to 98 wt% with respect to the total weight of the first positive electrode active material layer. The content of the second positive electrode active material included in the second positive electrode active material layer is, for example, 80 to 98 wt%, or 90 to 98 wt% with respect to the total weight of the second positive electrode active material layer.

[0052] The first positive electrode active material and / or the second positive electrode active material may include, for example, a composite positive electrode active material.

[0053] The composite positive electrode active material includes, for example, a core containing a lithium transition metal oxide, and a shell disposed along the surface of the core, and the shell has the chemical formula M a O b (0 < a ≤ 3, 0 < b < 4, if a is 1, 2, or 3, then b is not an integer) represents one or more first metal oxides and graphene, the first metal oxide is disposed in the graphene matrix, M is one or more metals selected from Groups 2 to 13, Group 15, and Group 16 of the periodic table of elements, the lithium transition metal oxide contains nickel, and the nickel content is 80 mol% or more with respect to the total number of moles of transition metals. A shell containing the first metal oxide and graphene is disposed on the core of the composite positive electrode active material.

[0054] Conventional graphene is difficult to uniformly coat on the core due to aggregation. In contrast, the composite positive electrode active material uses a composite containing a plurality of first metal oxides disposed in a graphene matrix to prevent the aggregation of graphene while a uniform shell is disposed on the core. Therefore, by effectively blocking the contact between the core and the electrolyte, side reactions due to the contact between the core and the electrolyte are prevented. Also, the reduction of nickel ions by the electrolyte (Ni 3+ ->Ni 2+) and cation mixing are suppressed, thereby suppressing the generation of a resistance layer such as a NiO phase. In addition, the elution of nickel ions is also suppressed. Since the shell containing graphene has flexibility, it easily accommodates the volume change of the composite positive electrode active material during charging and discharging, thereby suppressing the occurrence of cracks inside the composite positive electrode active material. Since graphene has high conductivity, the interface resistance between the composite positive electrode active material and the electrolyte is reduced. Therefore, despite the introduction of the shell containing graphene, the internal resistance of the lithium battery is maintained or reduced. In addition, since the first metal oxide has voltage resistance, it is possible to prevent the deterioration of the lithium transition metal oxide contained in the core during charging and discharging at high voltage. As a result, the cycle characteristics and high temperature stability of the lithium battery containing the composite positive electrode active material are improved. The shell may contain, for example, one type of first metal oxide or two or more different first metal oxides. In addition, the lithium transition metal oxide in the composite positive electrode active material has a high nickel content of 80 mol% or more relative to the total transition metal mole number, and a shell including the first metal oxide and graphene is disposed on the core, thereby providing high discharge capacity and cycle characteristics at the same time. Therefore, the composite positive electrode active material having a high nickel content of 80 mol% or more can provide improved capacity and still provide excellent life characteristics compared to a composite positive electrode active material having a relatively low nickel content. The metal contained in the first metal oxide may be, for example, one or more selected from Al, Nb, Mg, Sc, Ti, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn, Sb, and Se.

[0055] The first metal oxide is, for example, AlO z (0 <z<3)、NbO x (0 <x<2.5)、MgO x (0 <x<1)、Sc2O z (0 <z<3)、TiO y (0 <y<2)、ZrO y (0 <y<2)、V2O z (0 <z<3)、WO y (0 <y<2)、MnOy (0 < y < 2), Fe2O z (0 < z < 3), Co3O w (0 < w < 4), PdO x (0 < x < 1), CuO x (0 < x < 1), AgO x (0 < x < 1), ZnO x (0 < x < 1), Sb2O z (0 < z < 3), and SeO y (0 < y < 2) and is also one or more selected therefrom. By arranging such a first metal oxide in the graphene matrix, the uniformity of the shell arranged on the core is improved, and the voltage resistance of the composite positive electrode active material is further improved. For example, the shell contains, as the first metal oxide, Al2O x (0 < x < 3). The shell further contains one or more second metal oxides represented by the chemical formula M a O c (0 < a ≤ 3, 0 < c ≤ 4, when a is 1, 2, or 3, c is an integer). The M is one or more metals selected from Groups 2 to 13, Group 15, and Group 16 of the periodic table of elements. For example, the second metal oxide contains the same metal as the first metal oxide, and c / a, which is the ratio of c to a of the second metal oxide, has a value further greater than b / a, which is the ratio of b to a of the first metal oxide. For example, c / a > b / a. The second metal oxide is, for example, selected from Al2O3, NbO, NbO2, Nb2O5, MgO, Sc2O3, TiO2, ZrO2, V2O3, WO2, MnO2, Fe2O3, Co3O4, PdO, CuO, AgO, ZnO, Sb2O3, and SeO2. The first metal oxide is a reduction product of the second metal oxide. By reducing part or all of the second metal oxide, the first metal oxide is obtained. Therefore, the first metal oxide has a lower oxygen content and a higher oxidation number of the metal compared to the second metal oxide. For example, the shell is Al2O xIt contains (0 < x < 3) and Al2O3 which is the second metal oxide. In the composite cathode active material, for example, the transition metal of the graphene contained in the shell and the lithium transition metal oxide contained in the core are chemically bonded through a chemical bond. The carbon atom (C) of the graphene contained in the shell and the transition metal (Me) of the lithium transition metal oxide are chemically bonded through, for example, a C-O-Me bond (for example, a C-O-Ni bond) mediated by an oxygen atom. By chemically bonding the graphene contained in the shell and the lithium transition metal oxide contained in the core through a chemical bond, the core and the shell are complexed. Therefore, it is distinguished from a mere physical mixture of graphene and a lithium transition metal oxide. Also, the first metal oxide contained in the shell and the graphene are also chemically bonded through a chemical bond. Here, the chemical bond is, for example, a covalent bond or an ionic bond. The covalent bond is, for example, a bond containing at least one of an ester group, an ether group, a carbonyl group, an amide group, a carboxylic anhydride group, and an acid anhydride group. The ionic bond is, for example, a bond containing a carboxylate ion, an ammonium ion, an acyl cation group, etc. The thickness of the shell is, for example, 1 nm to 5 μm, 1 nm to 1 μm, 1 nm to 500 nm, 1 nm to 200 nm, 1 nm to 100 nm, 1 nm to 90 nm, 1 nm to 80 nm, 1 nm to 70 nm, 1 nm to 60 nm, 1 nm to 50 nm, 1 nm to 40 nm, 1 nm to 30 nm, 1 nm to 20 nm, or 1 nm to 10 nm. By having the shell with such a thickness range, an increase in the internal resistance of the lithium battery contained in the composite cathode active material is suppressed.

[0056] The content of the complex contained in the composite positive electrode active material is 3 wt% or less, 2 wt% or less, 1 wt% or less, 0.5 wt% or less, or 0.2 wt% or less of the total weight of the composite positive electrode active material. The content of the complex is 0.01 wt% to 3 wt%, 0.01 wt% to 1 wt%, 0.01 wt% to 0.7 wt%, 0.01 wt% to 0.6 wt%, 0.1 wt% to 0.5 wt%, 0.01 wt% to 0.2 wt%, 0.01 wt% to 0.1 wt%, or 0.03 wt% to 0.07 wt% of the total weight of the composite positive electrode active material. When the composite positive electrode active material contains a complex in such a range, the cycle characteristics of a lithium battery including the composite positive electrode active material are further improved. The average particle size of one or more selected from the first metal oxide and the second metal oxide contained in the composite may be 1 nm to 1 μm, 1 nm to 500 nm, 1 nm to 200 nm, 1 nm to 100 nm, 1 nm to 70 nm, 1 nm to 50 nm, 1 nm to 30 nm, 3 nm to 30 nm, 3 nm to 25 nm, 5 nm to 25 nm, 5 nm to 20 nm, or 7 nm to 20 nm. The first metal oxide and / or the second metal oxide may have such a nano-range particle size, so that they can be more uniformly distributed in the graphene matrix of the composite. Therefore, such a composite may be uniformly coated on the core without aggregation to form a shell. In addition, the first metal oxide and / or the second metal oxide may have such a particle size range, so that they may be more uniformly arranged on the core. Therefore, the first metal oxide and / or the second metal oxide may be uniformly arranged on the core, so that the withstand voltage characteristics may be more effectively exhibited. The average particle size of the first metal oxide and the second metal oxide may be measured, for example, using a measuring device of a laser diffraction method or a dynamic light scattering method. The average particle size is measured, for example, using a laser scattering particle size distribution analyzer (eg, HORIBA LA-920), and is the median diameter (D50) value when 50% is accumulated from the elementary particle side in volume conversion.

[0057] The core of the composite positive electrode active material may include, for example, a lithium transition metal oxide represented by the following formula 1:

[0058] [Chemical formula 1] Li a Nix Co y M z O 2-b A b

[0059] In the above Chemical Formula 1, 1.0 ≦ a ≦ 1.2, 0 ≦ b ≦ 0.2, 0.8 ≦ x < 1, 0 < y ≦ 0.3, 0 < z ≦ 0.3, and x + y + z = 1, M is one or more selected from the group consisting of manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), and boron (B), and A is F, S, Cl, Br, or a combination thereof.

[0060] The core contained in the composite positive electrode active material includes, for example, a lithium transition metal oxide represented by the following Chemical Formulas 2 to 4:

[0061] [Chemical Formula 2] LiNi x Co y Mn z O2

[0062] [Chemical Formula 3] LiNi x Co y Al z O2

[0063] In the above formula, 0.8 ≦ x ≦ 0.95, 0 < y ≦ 0.2, 0 < z ≦ 0.2, and x + y + z = 1.

[0064] [Chemical Formula 4] LiNi x Co y Al v Mn w O2

[0065] In the above formula, 0.8 ≦ x ≦ 0.95, 0 < y ≦ 0.2, 0 < v ≦ 0.2, 0 < w ≦ 0.2, and x + y + v + w = 1.

[0066] A lithium battery includes an electrolyte disposed between a plurality of positive electrodes and a plurality of negative electrodes, respectively.

[0067] The electrolyte contained in the lithium battery is, for example, a liquid electrolyte or a solid electrolyte. The solid electrolyte is, for example, an oxide-based solid electrolyte or a sulfide-based solid electrolyte.

[0068] Examples of the lithium battery include a lithium ion battery, a lithium solid-state battery, and a lithium air battery.

[0069] Referring to FIG. 1, a lithium battery 10000 includes an electrode group stack 1000 in which a plurality of positive electrodes 400, 401 and one or more negative electrodes 700 are alternately stacked in a thickness direction. The plurality of positive electrodes 400, 401 include a first positive electrode 400 and a second positive electrode 401. The first positive electrode 400 is an inner layer of the electrode group stack 1000, and the second positive electrode 401 is an outermost layer of the electrode group stack 1000. the first positive electrode current collector 200 and the first positive electrode active material layer 100 are disposed on both sides of the first positive electrode current collector 200; the second positive electrode 401 includes a second positive electrode current collector 201, a second positive electrode active material layer 101, and an interlayer 301 disposed between the second positive electrode current collector 201 and the second positive electrode active material layer 101; the second positive electrode current collector 201 includes a first surface and a second surface, the first surface facing the inner layer and the second surface being an opposite surface to the first surface; the second positive electrode active material layer 101 is disposed on the first surface and not on the second surface; and the thickness of the second positive electrode current collector 201 is equal to or smaller than the thickness of the first positive electrode current collector 200. The negative electrode 700 includes a negative electrode current collector 600 and a negative electrode active material layer 500. The number of first positive electrodes 400 and negative electrodes 700 may be 1 to 500, 1 to 400, 1 to 300, 1 to 200, 1 to 100, 1 to 50, or 1 to 30, independently of each other.

[0070] According to another embodiment, a lithium battery includes an electrode group stack in which a plurality of negative electrodes and one or more positive electrodes are alternately stacked in a thickness direction, the plurality of negative electrodes include a first negative electrode and a second negative electrode, the first negative electrode being an inner layer of the electrode group stack, and the second negative electrode being an outermost layer of the electrode group stack. the first negative electrode current collector includes a first negative electrode current collector and a first negative electrode active material layer, the first negative electrode active material layer being disposed on both sides of the first negative electrode current collector; the second negative electrode current collector includes a second negative electrode current collector, a second negative electrode active material layer, and an interlayer disposed between the second negative electrode current collector and the second negative electrode active material layer, the second negative electrode current collector includes a first surface and a second surface, the first surface facing the inner layer and the second surface being an opposite surface to the first surface, the second negative electrode active material layer being disposed on the first surface and not on the second surface, and a thickness of the second negative electrode current collector is equal to or smaller than a thickness of the first negative electrode current collector.

[0071] In the lithium battery of the present disclosure, the second negative electrode disposed in the outermost layer of the electrode group laminate includes an intermediate layer between the second negative electrode current collector and the second negative electrode active material layer, thereby suppressing bending of the second negative electrode. Therefore, the occurrence of defects such as curling and bending of the second negative electrode is suppressed during the manufacturing process of the electrode group laminate. In addition, the second negative electrode is a single-sided electrode, and the energy density of the lithium battery including the electrode group laminate is improved. In addition, the thickness of the second negative electrode current collector disposed in the second negative electrode is the same as the thickness of the first negative electrode current collector disposed in the first negative electrode, or the thickness of the second negative electrode current collector disposed in the second negative electrode is thinner than the thickness of the first negative electrode current collector disposed in the first negative electrode, thereby improving the energy density of the lithium battery. In addition, the occurrence of defects during the manufacturing process of the electrode group laminate is suppressed. Since the intermediate layer provides a bonding force between the second negative electrode current collector and the second negative electrode active material layer, the pressure required to bond the second negative electrode current collector and the second negative electrode active material layer during the manufacture of the second negative electrode is reduced, and thus warping of the second negative electrode is suppressed.

[0072] According to another embodiment, a method for manufacturing a lithium battery includes: dry-mixing a second positive electrode active material, a dry conductive material, and a dry binder to prepare a dry mixture; providing a second positive electrode current collector; disposing an intermediate layer on one surface of the second positive electrode current collector; and disposing the dry mixture on the intermediate layer and rolling it to manufacture a second positive electrode in which a second positive electrode active material layer is disposed on one surface of the second positive electrode current collector. The lithium battery includes an electrode group stack in which a plurality of positive electrodes and one or more negative electrodes are alternately stacked in a thickness direction, the plurality of positive electrodes include a first positive electrode and a second positive electrode, the first positive electrode being an inner layer of the electrode group stack, the second positive electrode being an outermost layer of the electrode group stack, and the second positive electrode being an outermost layer of the electrode group stack. the first positive electrode current collector includes a first positive electrode current collector and a first positive electrode active material layer, the first positive electrode active material layer being disposed on both sides of the first positive electrode current collector; the second positive electrode current collector includes a second positive electrode current collector and a second positive electrode active material layer, and an interlayer disposed between the second positive electrode current collector and the second positive electrode active material layer, the second positive electrode current collector includes a first surface and a second surface, the first surface facing the inner layer, the second surface being an opposite surface to the first surface, the second positive electrode active material layer being disposed on the first surface and not on the second surface, and the thickness of the second positive electrode current collector is equal to or smaller than the thickness of the first positive electrode current collector. The lithium battery manufactured by the above-mentioned manufacturing method can provide improved energy density by suppressing the generation of defects during the manufacturing process.

[0073] First, a second positive electrode is provided. The second positive electrode can be produced, for example, by the following method.

[0074] The method for manufacturing the second positive electrode includes the steps of dry-mixing a second positive electrode active material, a dry conductive material, and a dry binder to prepare a dry mixture, providing a second positive electrode current collector, disposing an intermediate layer on one surface of the second positive electrode current collector, and disposing and rolling the dry mixture on the intermediate layer to manufacture a second positive electrode having a second positive electrode active material layer disposed on one surface of the second positive electrode current collector. The second positive electrode active material is a dry positive electrode active material.

[0075] First, the second positive electrode active material, the dry conductive material, and the dry binder are dry-mixed to prepare a dry mixture. Dry mixing means mixing in a state in which no process solvent is included. The process solvent is, for example, a solvent used in the preparation of an electrode slurry. The process solvent is, for example, water, NMP, etc., but is not limited thereto, and is not particularly limited as long as it is a process solvent used in the preparation of an electrode slurry. The dry mixing may be performed at a temperature of, for example, 25 to 65°C using a stirrer. The dry mixing may be performed at a rotation speed of, for example, 10 to 10,000 rpm or 100 to 10,000 rpm using a stirrer. The dry mixing may be performed for, for example, 1 to 200 minutes or 1 to 150 minutes using a stirrer. The second positive electrode active material is a dry positive electrode active material.

[0076] The dry mixing may be performed, for example, one or more times. First, the second positive electrode active material, the dry conductive material, and the dry binder may be primarily dry mixed to prepare a first mixture. The primary dry mixing may be performed, for example, at a temperature of 25 to 65° C. and a rotation speed of 2000 rpm or less for a time period of 15 minutes or less. The primary dry mixing may be performed, for example, at a temperature of 25 to 65° C. and a rotation speed of 500 to 2000 rpm for a time period of 5 to 15 minutes. The electrode active material, the dry conductive material, and the dry binder may be uniformly mixed by the primary dry mixing. Then, the electrode active material, the dry conductive material, and the dry binder may be secondarily dry mixed to prepare a second mixture. The secondary dry mixing may be performed, for example, at a temperature of 25 to 65° C. and a rotation speed of 4000 rpm or more for a time period of 10 minutes or more. The secondary dry mixing may be carried out, for example, at a temperature of 25 to 65° C. and a rotation speed of 4000 to 9000 rpm for 10 to 60 minutes. A dry mixture containing a fibrillated dry binder is obtained by the secondary dry mixing.

[0077] The agitator is, for example, a kneader. The agitator includes, for example, a chamber, one or more rotating shafts disposed inside the chamber and rotating, and blades rotatably coupled to the rotating shafts and disposed in the longitudinal direction of the rotating shafts. The blades may be, for example, one or more selected from a ribbon blade, a sigma blade, a Z blade, a dispersion blade, and a screw blade. By including the blades, the electrode active material, the dry conductive material, and the dry binder can be effectively mixed without a solvent to produce a dough-like mixture.

[0078] The produced dry mixture can be put into an extrusion device and extruded into a sheet. The pressure during extrusion is, for example, 4 MPa to 100 MPa, or 10 MPa to 90 MPa. The obtained sheet-like extrudate is also a sheet for the second positive electrode active material layer.

[0079] Examples of the dry conductive material include, but are not limited to, carbon black, graphite particles, natural graphite, artificial graphite, acetylene black, ketjen black, carbon fibers, carbon nanotubes, metal powders or metal fibers or metal tubes of copper, nickel, aluminum, silver, etc., and conductive polymers such as polyphenylene derivatives. Any material used as a conductive material in the relevant technical field can be used. The conductive material is, for example, a carbon-based conductive material.

[0080] Dry binders that can be used include, but are not limited to, vinylidene fluoride / hexafluoropropylene copolymers, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), mixtures of the aforementioned polymers, and styrene-butadiene rubber-based polymers, as long as they are used in the relevant technical field.

[0081] A plasticizer or pore former may further be added to the electrode active material composition to form pores within the electrode plate.

[0082] The contents of the electrode active material, the dry conductive material, and the dry binder used in the electrode active material layer are as described above.

[0083] Next, a second positive electrode current collector is provided. The material of the second positive electrode current collector is as described above. The second positive electrode current collector is, for example, an aluminum foil.

[0084] Next, an intermediate layer is disposed on one surface of the second positive electrode current collector. In the step of disposing the intermediate layer on one surface of the second positive electrode current collector, the intermediate layer is disposed on one surface of the second positive electrode current collector by dry or wet method. For a specific disposing method, refer to the second positive electrode part including the intermediate layer described above. Alternatively, the intermediate layer may be disposed on both surfaces of the second positive electrode current collector.

[0085] Next, a sheet for the second positive electrode active material layer provided on the intermediate layer is placed and rolled to produce a second positive electrode in which the second positive electrode active material layer is placed on one side of the second positive electrode current collector. The intermediate layer is placed between the second positive electrode current collector and the second positive electrode active material layer. The rolling may be, for example, a roll press or a flat plate press, but is not necessarily limited to these. The pressure during rolling may be, for example, 0.1 ton / cm. 2 ~10.0ton / cm 2 If the pressure during rolling is too high, cracks may occur in the second positive electrode current collector, and if the pressure during rolling is too low, the bonding strength between the second positive electrode current collector and the second positive electrode active material layer may decrease.

[0086] Then, the first positive electrode is manufactured. The first positive electrode may be manufactured in the same manner as the second positive electrode. That is, the first positive electrode may be manufactured in a dry manner. Differently, the first positive electrode may be manufactured in a wet manner. The first positive electrode may be manufactured, for example, in the following exemplary manner, but is not necessarily limited to such a manner and may be adjusted according to required conditions.

[0087] A method for manufacturing a first positive electrode may include, for example, the steps of preparing a slurry by mixing a first positive electrode active material, a conductive material, a binder, and a process solvent, providing a first positive electrode current collector, and disposing the slurry on both sides of the first positive electrode current collector and rolling the slurry to manufacture a first positive electrode in which first positive electrode active material layers are disposed on both sides of the first positive electrode current collector.

[0088] First, a first positive electrode active material, a conductive material, a binder, and a process solvent are mixed to prepare a slurry for the first positive electrode.

[0089] The first positive electrode active material is as described above. The first positive electrode active material may be any material commonly used in the art, such as lithium metal oxide, without limitation. The first positive electrode may be, for example, the composite positive electrode active material described above as the first positive electrode active material.

[0090] Examples of the conductive material include, but are not limited to, carbon black, graphite particles, natural graphite, artificial graphite, acetylene black, ketjen black, carbon fibers, carbon nanotubes, metal powders or metal fibers or metal tubes such as copper, nickel, aluminum, and silver, and conductive polymers such as polyphenylene derivatives. In contrast, the first positive electrode does not include, for example, a separate conductive material.

[0091] Examples of binders that can be used include vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), mixtures of the aforementioned polymers, and styrene-butadiene rubber-based polymers, but are not limited to these. Any binder that is used in the relevant technical field can be used.

[0092] Examples of process solvents that can be used include, but are not limited to, N-methylpyrrolidone (NMP), acetone, water, etc., and any process solvents that are used in the art can be used.

[0093] A plasticizer or a pore-forming agent may be further added to the slurry for the first positive electrode to form pores inside the first positive electrode.

[0094] The contents of the first positive electrode active material, conductive material, and binder used in the manufacture of the first positive electrode are, for example, within the ranges used in the second positive electrode. Depending on the application and configuration of the first positive electrode, one or more of the conductive material and the binder may be omitted.

[0095] The content of the binder in the first positive electrode is 0.1 to 10 wt% or 0.1 to 5 wt% of the total weight of the first positive electrode active material layer. The content of the first positive electrode active material in the first positive electrode is 90 wt% to 99 wt% or 95 wt% to 99 wt% of the total weight of the first positive electrode active material layer.

[0096] Next, a first positive electrode current collector is provided. The material of the first positive electrode current collector is as described above. The first positive electrode current collector is, for example, an aluminum foil. The thickness of the first positive electrode current collector is, for example, thicker than that of the second positive electrode current collector.

[0097] Then, the first positive electrode slurry is disposed on both sides of the first positive electrode collector and rolled to manufacture a first positive electrode having a first positive electrode active material layer disposed on both sides of the first positive electrode collector. For example, the first positive electrode slurry is prepared by mixing the first positive electrode active material, the conductive material, the binder, and the process solvent, and the first positive electrode is manufactured by coating the first positive electrode slurry on both sides of the aluminum current collector. Alternatively, the first positive electrode slurry is cast on a separate support, and the first positive electrode sheet peeled off from the support is laminated on both sides of the aluminum current collector to manufacture the first positive electrode.

[0098] The negative electrode is then prepared as follows.

[0099] The negative electrode is manufactured in a substantially similar manner to the first positive electrode, except that, for example, a negative electrode active material is used instead of the first positive electrode active material. For example, a negative electrode active material, a conductive material, a binder, and a process solvent are mixed to manufacture a negative electrode active material composition, which is then directly coated on a copper current collector to manufacture a negative electrode plate. Alternatively, the manufactured negative electrode active material composition is cast on a separate support, and the negative electrode active material sheet peeled off from the support is laminated on a copper current collector to manufacture a negative electrode plate. Alternatively, the negative electrode may be manufactured by a dry process, like the second positive electrode.

[0100] The negative electrode active material can be any material used as a negative electrode active material for lithium batteries in the art. For example, it includes at least one selected from the group consisting of lithium metal, metals capable of being alloyed with lithium, transition metal oxides, non-transition metal oxides, and carbon-based materials. The metals capable of being alloyed with lithium include, for example, Si, Sn, Al, Ge, Pb, Bi, SbSi-Y alloy (wherein Y is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, or a combination thereof, but is not Si), Sn-Y alloy (wherein Y is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, or a combination thereof, but is not Sn), etc. The element Y is, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof. The transition metal oxide is, for example, lithium titanium oxide, vanadium oxide, lithium vanadium oxide, etc. The non-transition metal oxide is, for example, SnO2, SiO xIt is, for example, (0 < x < 2). The carbon-based material is, for example, crystalline carbon, amorphous carbon, or a mixture thereof. The crystalline carbon is, for example, graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite. The amorphous carbon is, for example, soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, calcined coke, and the like.

[0101] The types of conductive material, binder, and process solvent used in the production of the negative electrode are also materials commonly used in the production of lithium batteries. The types of conductive material, binder, and process solvent used in the production of the negative electrode can be selected from among the materials used in the production of the first positive electrode.

[0102] The contents of the negative electrode active material, conductive material, binder, and process solvent used in the production of the negative electrode are at levels commonly used in lithium batteries. Depending on the use and configuration of the negative electrode, one or more of the conductive material, binder, and process solvent can be omitted.

[0103] The negative electrode current collector is, for example, a copper foil.

[0104] The binder content contained in the negative electrode is, for example, 0.1 to 10 wt% or 0.1 to 5 wt% of the total weight of the negative electrode active material layer. The conductive material content contained in the negative electrode is, for example, 0.1 to 10 wt% or 0.1 to 5 wt% of the total weight of the negative electrode active material layer. The negative electrode active material content contained in the negative electrode is, for example, 80 wt% to 98 wt% or 90 wt% to 95 wt% of the total weight of the negative electrode active material layer. When the negative electrode active material is lithium metal, the negative electrode does not contain a binder and a conductive material.

[0105] Next, a separator is provided between the first positive electrode and the negative electrode, and between the second positive electrode and the negative electrode.

[0106] The separator may be any separator that is generally used in lithium batteries. For example, a separator that has low resistance to ion movement of the electrolyte and is excellent in electrolyte impregnation ability is used. The separator may be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, and may be in the form of a nonwoven fabric or a woven fabric. For example, a rollable separator such as polyethylene or polypropylene is used for a lithium ion battery, and a separator that has excellent organic electrolyte impregnation ability is used for a lithium ion polymer battery.

[0107] The separator is manufactured by the following exemplary method, but is not necessarily limited to such method, and may be adjusted according to the required conditions.

[0108] First, a separator composition is prepared by mixing a polymer resin, a filler, and a solvent. The separator composition is directly coated on the top of an electrode and dried to form a separator. Alternatively, the separator composition is cast on a support and dried, and the separator film is peeled off from the support and laminated on the top of an electrode to form a separator.

[0109] The polymer used for the separator is not particularly limited, and any polymer used as a binder for electrode plates can be used, such as vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, or a mixture thereof.

[0110] The electrolyte is then applied.

[0111] The electrolyte is, for example, an organic electrolyte solution, which is produced by dissolving a lithium salt in an organic solvent, for example.

[0112] The organic solvent can be any organic solvent used in the art. The organic solvent can be, for example, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethylsulfoxide, dioxane, 1,2-dimethoxyethane, sulfolane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a mixture thereof.

[0113] Any lithium salt may be used as long as it is used as a lithium salt in the art. Examples of the lithium salt include LiPF, LiBF, LiSbF, LiAsF, LiClO, LiCF, Li(CFSO)N, LiC, F, SO, LiAlO, LiAlCl, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (x, y are each 1 to 20), LiCl, LiI, or a mixture thereof.

[0114] Meanwhile, the electrolyte is a solid electrolyte. The solid electrolyte is, for example, boron oxide, lithium oxynitride, etc., but is not limited thereto, and any solid electrolyte used as a solid electrolyte in the art can be used. The solid electrolyte is formed on the negative electrode by a method such as sputtering, or a separate solid electrolyte sheet is laminated on the negative electrode. The solid electrolyte is, for example, an oxide-based solid electrolyte or a sulfide-based solid electrolyte. When a solid electrolyte is used, the separator may be omitted.

[0115] Referring to FIG. 4, a lithium battery 1 according to an embodiment includes a positive electrode 3, a negative electrode 2, and a separator 4. The separator 4 is disposed between the positive electrode 3 and the negative electrode 2 to form a battery structure. The battery structure 7 is stacked in a bi-cell structure and then housed in a battery case 5. The stacked structure of the battery structure 7 is not limited to a bi-cell. The battery structure 7 may include an electrode tab 8 that serves as an electrical path for conducting a current formed in the battery structure 7 to the outside. An organic electrolyte is injected into the battery case 5 and sealed to complete the lithium battery 1. The battery case 5 is rectangular, but is not necessarily limited to such a shape and may be, for example, cylindrical or thin film.

[0116] The pouch-type lithium battery corresponds to the lithium battery of FIG. 4 in which a pouch is used as a battery case. The pouch-type lithium battery includes one or more battery structures. A separator is disposed between a positive electrode and a negative electrode to form a battery structure. The battery structures are stacked in a bi-cell structure, and then impregnated with an organic electrolyte, housed in a pouch, and sealed to complete the pouch-type lithium battery. For example, although not shown in the drawings, the above-mentioned positive electrode, negative electrode, and separator are simply stacked and housed in a pouch in the form of an electrode assembly. Then, an organic electrolyte is injected into the pouch and sealed to complete the lithium battery.

[0117] Lithium batteries have excellent life characteristics and high rate characteristics, and are therefore used, for example, in electric vehicles (EVs), hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs), and fields requiring large amounts of power storage, such as electric bicycles and power tools.

[0118] A plurality of lithium batteries are stacked to form a battery module, and a plurality of battery modules form a battery pack. Such a battery pack can be used in all devices requiring high capacity and high output, such as notebook computers, smartphones, and electric vehicles. The battery module includes, for example, a plurality of batteries and a frame that holds them. The battery pack includes, for example, a plurality of battery modules and bus bars that connect them. The battery module and / or the battery pack may further include a cooling device. The plurality of battery packs are regulated by a battery management system. The battery management system includes a battery pack and a battery control device connected to the battery pack.

[0119] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the examples are merely for the purpose of illustrating the present invention and are not intended to limit the scope of the present invention.

[0120] (Lithium battery manufacturing) Example 1: Inner layer wet type first positive electrode (both sides), outermost layer dry type second positive electrode (single side), thickness of first positive electrode current collector>thickness of second positive electrode current collector (Manufacture of the first positive electrode) LiNi 0.91 Co 0.05 Al 0.04 A mixture of a first positive electrode active material O2 (hereinafter referred to as NCA91), a carbon conductive agent (Denka Black), and polyvinylidene fluoride (PVdF) in a weight ratio of 96:1.8:2.2 was mixed with N-methylpyrrolidone (NMP) in an agate mortar to prepare a slurry. The slurry was bar coated on both sides of an aluminum thin film having a thickness of 15 μm, dried at room temperature, and then dried again under vacuum at 120° C. to prepare a laminate in which a first positive electrode active material layer was introduced on both sides of a first positive electrode current collector. The laminate was rolled to prepare a first positive electrode. The thickness of the first positive electrode active material layer disposed on one side of the first positive electrode current collector was 90 μm. The mixture density of the first positive electrode active material layer was 3.6 g / cm 3 It was.

[0121] The first positive electrode had a structure of first positive electrode active material layer / first positive electrode current collector / first positive electrode active material layer.

[0122] (Manufacture of the second positive electrode) LiNi as the second positive electrode active material 0.91 Co 0.05 Al 0.04 O2 (hereinafter referred to as large diameter NCA91), a carbon conductive material (Denka Black) as a dry conductive material, and polytetrafluoroethylene (PTFE) as a dry binder were charged into a blade mixer in a weight ratio of 96:1.8:2.2, and then primary dry mixing was performed at 25°C and 1000 rpm for 10 minutes to prepare a first mixture in which the positive electrode active material, conductive material, and binder were uniformly mixed.

[0123] Then, in order to promote fiberization of the binder, the first mixture was further mixed at 25° C. and 5000 rpm for 20 minutes to prepare a second mixture. No separate solvent was used when preparing the first and second mixtures.

[0124] The prepared second mixture was put into an extruder and extruded to prepare a sheet-shaped positive electrode active material layer self-standing film. The pressure during extrusion was 50 MPa.

[0125] A carbon layer was disposed as an interlayer on one surface of a 12 μm-thick aluminum thin film, and the interlayer was disposed on one surface of a second positive electrode current collector to form a first laminate.

[0126] The intermediate layer was prepared by coating a composition containing a carbon conductive material (Danka black) and polyvinylidene fluoride (PVDF) on an aluminum thin film and then drying it. The thickness of the intermediate layer disposed on one side of the aluminum thin film was about 1 μm.

[0127] A laminate was produced by disposing a positive electrode active material layer free-standing film on the intermediate layer of the produced first laminate, and the produced laminate was rolled to produce a second positive electrode.

[0128] The thickness of the second positive electrode active material layer was 100 μm. The mixture density of the second positive electrode active material layer was 3.0 g / cm 3 It was.

[0129] The second positive electrode had a structure of second positive electrode current collector / intermediate layer / second positive electrode active material layer.

[0130] As shown in FIG. 2, the second positive electrode had a substantially flat sheet shape.

[0131] (Production of negative electrodes) Artificial graphite (BSG-L, Tianjin BTR New Energy Technology Co., Ltd.), styrene butadiene rubber (SBR) binder (ZEON), and carboxymethyl cellulose (CMC, NIPPON A&L) were mixed in a weight ratio of 98:1:1, then added to distilled water and stirred for 60 minutes using a mechanical stirrer to prepare anode active material slurry. The prepared slurry was applied to both sides of 10μm thick copper foil using a doctor blade to a thickness of about 60μm, dried in a hot air dryer at 100℃ for 0.5 hours, and then dried again in a vacuum at 120℃ for 4 hours to prepare a laminate. The prepared laminate was roll pressed to prepare anode.

[0132] The negative electrode had a structure of negative electrode active material layer / negative electrode current collector / negative electrode active material layer.

[0133] (Manufacturing of electrode group laminate) After the first positive electrodes and negative electrodes were alternately stacked, second positive electrodes were disposed in the uppermost and lowermost layers, respectively, to prepare an electrode group stack.

[0134] The electrode group laminate had a structure of second positive electrode / negative electrode / first positive electrode / negative electrode / ... / negative electrode / first positive electrode / negative electrode / second positive electrode along the thickness direction. Separators were placed between the first positive electrode and the negative electrode, and between the second positive electrode and the negative electrode.

[0135] Since the second positive electrode has a substantially flat sheet shape, it was easy to align it with the negative electrode in the stacked assembly. No curling occurred in the second positive electrode during the manufacturing process of the stacked assembly.

[0136] (Pouch cell manufacturing) The electrode group laminate prepared above was placed in an aluminum laminate bag, and an electrolyte, which was a solution of 1.3M LiPF6 dissolved in EC (ethylene carbonate) + EMC (ethyl methyl carbonate) + DMC (dimethyl carbonate) (volume ratio 3:4:3), was added and vacuum sealed to prepare a pouch cell. Positive and negative terminals were extended to the outside of the pouch cell.

[0137] Example 2: Inner layer dry type first positive electrode (both sides), outermost layer dry type second positive electrode (single side), thickness of first positive electrode current collector>thickness of second positive electrode current collector A lithium battery was manufactured in the same manner as in Example 1, except that a dry positive electrode was used as the first positive electrode instead of the wet positive electrode.

[0138] An aluminum thin film having a thickness of 15 μm was used as the first positive electrode current collector.

[0139] The first positive electrode had a structure of first positive electrode active material layer / intermediate layer / first positive electrode current collector / intermediate layer / first positive electrode active material layer.

[0140] Since the second positive electrode has a substantially flat sheet shape, it was easy to align it with the negative electrode in the stacked assembly. No curling occurred in the second positive electrode during the manufacturing process of the stacked assembly.

[0141] Therefore, no defects occur during the manufacturing process of the lithium battery.

[0142] Comparative Example 1: Inner layer wet type first positive electrode (both sides), outermost layer wet type second positive electrode (single side), thickness of first positive electrode current collector>thickness of second positive electrode current collector A lithium battery was manufactured in the same manner as in Example 1, except that a second positive electrode prepared by a wet method instead of a dry method was used.

[0143] The second positive electrode was produced by the following method.

[0144] (Manufacture of the second positive electrode) LiNi 0.91 Co 0.05 Al 0.04 A mixture of a second positive electrode active material O2 (hereinafter referred to as NCA91), a carbon conductive agent (Denka Black), and polyvinylidene fluoride (PVdF) in a weight ratio of 96:1.8:2.2 was mixed with N-methylpyrrolidone (NMP) in an agate mortar to prepare a slurry. The slurry was bar coated on one side of an aluminum thin film having a thickness of 12 μm, dried at room temperature, and then dried again under vacuum at 120° C. to prepare a laminate in which a second positive electrode active material layer was introduced on one side of a second positive electrode current collector. The laminate was rolled to prepare a second positive electrode. The thickness of the second positive electrode active material layer disposed on one side of the second positive electrode current collector was 100 μm. The mixture density of the second positive electrode active material layer was 3.0 g / cm 3 It was.

[0145] The second positive electrode had a structure of a second positive electrode current collector / a second positive electrode active material layer. As shown in FIG. 3, the second positive electrode had a sheet shape that was significantly curved by rolling.

[0146] Since the second positive electrode has a curved sheet shape, it is very difficult to align it with the negative electrode in the stacked assembly, and therefore, the second positive electrode curls during the manufacturing process of the stacked assembly, making it difficult to manufacture the stacked assembly.

[0147] Thus, defects occurred during the manufacturing process of the lithium battery.

[0148] Comparative Example 2: Inner layer wet type first positive electrode (both sides), outermost layer wet type second positive electrode (single side), thickness of first positive electrode current collector>thickness of second positive electrode current collector, thickness of first positive electrode active material layer>thickness of second positive electrode active material layer A lithium battery was manufactured in the same manner as in Example 1, except that a second positive electrode prepared by a wet method instead of a dry method was used and the thickness of the second positive electrode active material layer included in the second positive electrode was changed from 100 μm to 80 μm.

[0149] For the method of producing the second positive electrode, refer to Comparative Example 1.

[0150] The second positive electrode had a structure of a second positive electrode current collector / a second positive electrode active material layer. The second positive electrode had a sheet shape that was significantly curved by rolling.

[0151] Since the second positive electrode has a curved sheet shape, it is very difficult to align it with the negative electrode in the stacked assembly, and therefore, the second positive electrode curls during the manufacturing process of the stacked assembly, making it difficult to manufacture the stacked assembly.

[0152] In addition, the thicknesses of the second positive electrode current collector and the second positive electrode active material layer were reduced, and as a result, partial cracks were generated in the second positive electrode current collector and the second positive electrode active material layer during the rolling process.

[0153] Thus, defects occurred during the manufacturing process of the lithium battery.

[0154] Comparative Example 3: Inner layer wet type first positive electrode (both sides), outermost layer wet type second positive electrode (single side), thickness of first positive electrode current collector>thickness of second positive electrode current collector, mixture density of first positive electrode active material layer<mixture density of second positive electrode active material layer A second positive electrode manufactured by a wet method instead of a dry method was used, and the mixture density of the second positive electrode active material layer contained in the second positive electrode was set to 3.0 g / cm 3 from 3.9 g / cm 3 A lithium battery was manufactured in the same manner as in Example 1, except that the above-mentioned procedure was changed to the above.

[0155] For the method of producing the second positive electrode, refer to Comparative Example 1.

[0156] The second positive electrode had a structure of a second positive electrode current collector / a second positive electrode active material layer. The second positive electrode had a sheet shape that was significantly curved by rolling.

[0157] Since the second positive electrode has a curved sheet shape, it is very difficult to align it with the negative electrode in the stacked assembly, and therefore, the second positive electrode curls during the manufacturing process of the stacked assembly, making it difficult to manufacture the stacked assembly.

[0158] In addition, the thickness of the second positive electrode current collector was reduced and the mix density of the second positive electrode active material layer was increased, resulting in partial cracks occurring in the second positive electrode current collector and the second positive electrode active material layer during the rolling process.

[0159] Thus, defects occurred during the manufacturing process of the lithium battery.

[0160] Comparative Example 4: Outermost dry second positive electrode excluded A lithium battery was manufactured in the same manner as in Example 1, except that the second positive electrode was not used during the manufacture of the electrode group stack, and the electrode group stack was produced using only the first positive electrode and the negative electrode.

[0161] Comparative Example 5: Inner layer wet type first positive electrode (both sides), outermost layer dry type second positive electrode (single side), no coating layer (free) A lithium battery was manufactured in the same manner as in Example 1, except that a second positive electrode was manufactured using a 12 μm thick aluminum thin film not coated with a carbon layer as a second positive electrode current collector.

[0162] In the produced second positive electrode, a portion of the second positive electrode active material layer was present in a peeled state from the second positive electrode current collector.

[0163] Therefore, it was not possible to manufacture a pouch cell in which the second positive electrode is disposed in the outermost layer of the electrode group stack.

[0164] Evaluation Example 1: Evaluation of the vertical adhesion strength of the positive electrode active material layer (I) The binding properties of the positive electrode active material layers included in the second positive electrodes prepared in Example 1 and Comparative Example 1 were analyzed using SAICAS (SAICAS EN-EX, Daipla Wintes, JAPAN).

[0165] A constant speed analysis was performed using a 1mm wide diamond blade with a clearance angle of 10°, a rake angle of 20°, a shear angle of 45°, a horizontal velocity of 4μm / s, and a vertical velocity of 0.4μm / s to measure the vertical adhesion force (F V , Vertical Force) was measured.

[0166] First, a first constant-rate analysis was performed from a first position on the surface of the positive active material layer to the surface of the positive current collector, and the positive active material layer was removed by moving the blade horizontally along the surface of the positive current collector. Then, a second constant-rate analysis was performed under the same conditions as the first constant-rate analysis at a position 10 μm back from the first position. The data measured in the second constant-rate analysis was used.

[0167] The vertical adhesive strength of the positive active material layer was measured, and the measured data was normalized to the adhesive strength graph area to obtain the vertical relative adhesive strength (F VR , Vertical Relative Force) was derived.

[0168] The vertical adhesive strength of the positive electrode active material layer was measured from a first point 5% away from the surface of the positive electrode active material layer to a second point 5% away from the surface of the electrode current collector with respect to the total thickness of the positive electrode active material layer. That is, data near the surface of the positive electrode active material layer and near the surface of the electrode current collector were excluded to prevent measurement errors.

[0169] The vertical relative adhesive strength (F VR , Vertical Relative Force) data, the vertical adhesive force (F VR The rate of change in the vertical relative force (F VR Arithmetic mean values ​​were also calculated from the Vertical Relative Force (VRF) data.

[0170] [Formula 1] Vertical relative adhesive force (F VR , Vertical Relative Force) change rate = [(Maximum vertical relative force - Minimum vertical relative force) / Minimum vertical relative force] x 100

[0171] [Table 1]

[0172] As shown in Table 1, the rate of change in the vertical relative adhesive strength of the positive electrode active material layer included in the second positive electrode of Example 1 was 200% or less.

[0173] Therefore, it was confirmed that the positive electrode active material layer had uniform binding strength and composition distribution regardless of the position in the thickness direction.

[0174] In contrast, the positive electrode active material layer contained in the second positive electrode of Comparative Example 1 had a rate of change in the vertical adhesive strength of more than 1000%.

[0175] Therefore, it was confirmed that the positive electrode active material layer included in the second positive electrode of Comparative Example 1 had a binding strength and composition distribution that significantly changed depending on the position in the thickness direction.

[0176] Evaluation Example 2: Evaluation of the horizontal adhesion strength of the positive electrode active material layer (II) The binding properties of the positive electrode active material layers included in the second positive electrodes prepared in Example 1 and Comparative Example 1 were analyzed using SAICAS (SAICAS EN-EX, Daipla Wintes, JAPAN).

[0177] A constant speed analysis was performed using a 1mm wide diamond blade with a clearance angle of 10°, a rake angle of 20°, a shear angle of 45°, a horizontal velocity of 4μm / s, and a vertical velocity of 0.4μm / s to measure the horizontal adhesion force (F H2 , Horizontal Force) were measured.

[0178] First, a first constant-rate analysis was performed from a first position on the surface of the positive active material layer to the surface of the positive current collector, and the positive active material layer was removed by moving the blade horizontally along the surface of the positive current collector. Then, a second constant-rate analysis was performed under the same conditions as the first constant-rate analysis at a position 10 μm back from the first position. The data measured in the second constant-rate analysis was used.

[0179] A first horizontal adhesive strength (F) at a first point 10% away from the surface of the positive electrode active material layer with respect to the total thickness of the positive electrode active material layer H1 , Horizontal Force) and a second horizontal adhesion force (F H2 , Horizontal Force) were measured.

[0180] The ratio of the horizontal adhesive force between the first point and the second point is defined by the following Equation 2.

[0181] [Formula 2] Ratio of horizontal adhesion force between point 1 and point 2 (%) = [F H2 / F H1 ] x 100

[0182] [Table 2]

[0183] As shown in Table 2, the horizontal relative binding strength ratio of the positive electrode active material layer included in the second positive electrode of Example 1 was 70% or more.

[0184] In contrast to this, the ratio of the horizontal bonding strength of the positive electrode active material layer contained in the second positive electrode of Comparative Example 1 was less than 50%.

[0185] That is, the ratio of the horizontal relative binding strength of the positive electrode active material layer included in the second positive electrode of Example 1 was increased compared to that of the positive electrode active material layer of Comparative Example 1.

[0186] Therefore, it was confirmed that the positive electrode active material layer included in the second positive electrode of Example 1 had a more uniform binding strength and composition distribution than the positive electrode active material layer included in the second positive electrode of Comparative Example 1.

[0187] Evaluation example 3: Evaluation of surface roughness of positive electrode current collector The cross sections of the second positive electrodes prepared in Example 1 and Comparative Example 1 were measured using a scanning electron microscope, and the surface roughness of the second positive electrode current collector was measured from the cross-sectional image using software.

[0188] Some of the measurement results are shown in Table 3 below.

[0189] [Table 3]

[0190] As shown in Table 3, the surface of the second positive electrode current collector included in the wet second positive electrode prepared in Comparative Example 1 had an R of more than 3.5 μm. max , R exceeding 2.3μm a , R exceeding 2.3μm q The values ​​were shown.

[0191] From the scanning electron microscope image of the cross section of the wet second positive electrode of Comparative Example 1, it was found that the increased pressing pressure caused the positive electrode active material particles to penetrate into the second positive electrode current collector, resulting in the formation of unevenness on the surface of the second positive electrode current collector.

[0192] As shown in Table 3, the surface of the second positive electrode current collector included in the dry type second positive electrode prepared in Example 1 exhibited reduced surface roughness.

[0193] From a scanning electron microscope image of a cross section of the dry second positive electrode of Example 1, it was found that the positive electrode active material particles did not penetrate into the second positive electrode current collector due to the reduced pressing pressure, and therefore almost no unevenness was formed on the surface of the second positive electrode current collector.

[0194] Although the dry type second positive electrode of Example 1 uses a thin film current collector, no cracks or the like in the thin film current collector were found.

[0195] Evaluation example 4: Peel strength evaluation For each of the second positive electrodes prepared in Example 1, Comparative Example 1, and Comparative Example 5, the positive electrode was cut to 25 mm x 150 mm and fixed to the center of a 30 mm x 200 mm slide glass using tape, and then the current collector was peeled off from the positive electrode active material layer using a Universal Test Machine (UTM) to measure the 90° peel strength. Some of the measurement results are shown in Table 4 below.

[0196] [Table 4]

[0197] As shown in Table 4, the positive electrode of Example 1 exhibited a binding strength of 1 gf / mm. Therefore, the positive electrode of Example 1 exhibited high binding strength, even though the second positive electrode current collector surface had a low surface roughness as shown in Evaluation Example 3.

[0198] The positive electrode of Comparative Example 1 also exhibited excellent binding strength, but as shown in Evaluation Example 3, such binding strength was obtained due to the positive electrode active material having a high surface roughness on the second positive electrode current collector surface.

[0199] In the second positive electrode of Comparative Example 6, a part of the positive electrode active material layer was present in a state of being peeled off from the second positive electrode current collector before the peel strength evaluation, and therefore the peel strength evaluation was impossible.

[0200] Evaluation example 5: Lithium deposition evaluation The lithium batteries prepared in Example 1, Example 2, and Comparative Example 4 were charged at 25° C. at a constant current of 0.1 C rate until the voltage reached 4.4 V (vs. Li), and then cut off at a current of 0.05 C rate while maintaining 4.4 V in constant voltage mode. Then, they were discharged at a constant current of 0.1 C rate until the voltage reached 2.8 V (vs. Li) during discharge (formation cycle).

[0201] The lithium battery that had undergone the chemical cycle was charged at a constant current of 0.5C rate at 25°C until the voltage reached 4.4V (vs. Li). It was then discharged at a constant current of 0.5C rate until the voltage reached 2.8V (vs. Li) during discharge. This cycle was repeated 100 times. th The cycle was repeated under the same conditions (100 times). In all charge / discharge cycles, a 10-minute rest period was provided after each charge / discharge cycle.

[0202] After the charging and discharging were completed, the battery was disassembled and the deposition of lithium (Li) on the surface of the negative electrode was evaluated. The experimental results are shown in Table 5 below.

[0203] [Table 5]

[0204] As shown in Table 5, in the lithium batteries of Examples 1 and 2 in which the second positive electrode was disposed in the outermost layer of the electrode group laminate, no lithium deposition occurred on the surface of the negative electrode.

[0205] In contrast, in the lithium battery of Comparative Example 4, which did not include an outermost second positive electrode, lithium deposition on the negative electrode surface was confirmed. [Explanation of symbols]

[0206] 1 Lithium battery 2 negative electrode 3 Positive electrode 4. Separator 5 Battery case 7 Battery structure 8 Electrode tab 100 First positive electrode active material layer 101 Second positive electrode active material layer 200 First positive electrode current collector 201 Second positive electrode current collector 301 Middle Class 400 1st positive electrode 401 2nd positive electrode 500 Negative electrode active material layer 600 Negative electrode current collector 700 negative electrode 1000 Electrode group laminate 10000 Lithium Battery

Claims

1. The battery includes an electrode group stack in which a plurality of positive electrodes and one or more negative electrodes are alternately stacked in a thickness direction, the plurality of positive electrodes includes a first positive electrode and a second positive electrode, the first positive electrode is an inner layer of the electrode group stack, the second positive electrode is an outermost layer of the electrode group stack, the first positive electrode includes a first positive electrode current collector and a first positive electrode active material layer, the first positive electrode active material layer being disposed on both sides of the first positive electrode current collector; the second positive electrode includes a second positive electrode current collector, a second positive electrode active material layer, and an interlayer disposed between the second positive electrode current collector and the second positive electrode active material layer, the second positive electrode current collector includes a first surface and a second surface, the first surface facing the inner layer, and the second surface being an opposite surface to the first surface; the second positive electrode active material layer is disposed on the first surface and is not disposed on the second surface, The thickness of the second positive electrode current collector is thinner than the thickness of the first positive electrode current collector, the second positive electrode active material layer is thicker than the first positive electrode active material layer.

2. 2. The lithium battery according to claim 1, wherein a ratio of a thickness of the first positive electrode current collector to a thickness of the second positive electrode current collector is 1:0.2 or more and less than 1:

1.

3. The maximum roughness depth (R max ) is greater than the maximum roughness of the surface of the second positive electrode current collector; The mean roughness (R a ) is greater than the average roughness of the surface of the second positive electrode current collector, 2. The lithium battery of claim 1, wherein the root mean square (RMS) roughness (Rq) of the first positive current collector surface is greater than the root mean square roughness of the second positive current collector surface.

4. The maximum roughness (R max ) is 3 μm or less, The average roughness (R a ) is 2 μm or less, The root mean square roughness (R q 2. The lithium battery of claim 1, wherein the average particle diameter is 2 μm or less.

5. 2. The lithium battery of claim 1, wherein the intermediate layer comprises a binder, the binder comprising one or more selected from a conductive binder and a non-conductive binder, the binder comprising a fluorine-based binder.

6. 10. The lithium battery of claim 1, wherein the intermediate layer comprises a carbon-based conductive material.

7. 2. The lithium battery according to claim 1, wherein the thickness of the intermediate layer is 0.01% to 30% of the thickness of the second positive electrode current collector.

8. 2. The lithium battery of claim 1, wherein the second positive electrode active material layer comprises a second positive electrode active material and a binder, the second positive electrode active material being a dry positive electrode active material and the binder being a dry binder.

9. 9. The lithium battery of claim 8, wherein the dry binder comprises a fibrillized binder, and wherein the dry binder comprises a fluorine-based binder.

10. 9. The lithium battery of claim 8, wherein the second positive electrode active material layer further comprises a conductive material, the conductive material being a dry conductive material, the dry conductive material comprising a carbon-based conductive material.

11. 11. The lithium battery of claim 10, wherein the carbon-based conductive material comprises a fibrous conductive material, the fibrous conductive material comprising carbon nanotubes, carbon fibers, or a mixture thereof.

12. 2. The lithium battery of claim 1, wherein the second positive electrode active material layer is a self-standing film and is free of residual processing solvents.

13. A lithium battery as described in claim 1, wherein the ratio of the thickness of the first positive electrode active material layer to the thickness of the second positive electrode active material layer is greater than 1:1 and less than 1:

3.

14. The second positive electrode active material layer has a mixture density equal to or lower than the mixture density of the first positive electrode active material layer; 2. The lithium battery according to claim 1, wherein a ratio of a mixture density of the first positive electrode active material layer to a mixture density of the second positive electrode active material layer is 1:0.5 to 1:

1.

15. The second positive electrode active material layer has a vertical relative adhesive strength (F) depending on a depth from a first point that is 5% apart from a surface of the second positive electrode active material layer in a direction toward the second positive electrode current collector to a second point that is 5% apart from a surface of the second positive electrode current collector with respect to a total thickness of the second positive electrode active material layer when measured by a surface and interfacial cutting analysis system (SAICAS). VR 2. The lithium battery according to claim 1, wherein the rate of change of the load (V) is 300% or less.

16. The second positive electrode active material layer has a first horizontal adhesion (F ) at a first point that is 10% apart from a surface of the second positive electrode active material layer in a second positive electrode current collector direction with respect to an entire thickness of the second positive electrode active material layer when measured by SAICAS. H1 A second horizontal force (F , Horizontal Force) at a second point 10% away from the surface of the second positive electrode current collector H2 2. The lithium battery according to claim 1, wherein the ratio of the horizontal adhesive force (H, Horizontal Force) is 50% or more.

17. 10. The lithium battery of claim 1, further comprising an electrolyte disposed between the plurality of positive electrodes and the plurality of negative electrodes, respectively.

18. 18. The lithium battery according to claim 17, wherein the electrolyte is a liquid electrolyte or a solid electrolyte.

19. The battery includes an electrode group stack in which a plurality of negative electrodes and one or more positive electrodes are alternately stacked in a thickness direction, the plurality of negative electrodes includes a first negative electrode and a second negative electrode, The first negative electrode is an inner layer of the electrode group stack, the second negative electrode is an outermost layer of the electrode group stack, the first negative electrode includes a first negative electrode current collector and a first negative electrode active material layer, the first negative electrode active material layer being disposed on both sides of the first negative electrode current collector; the second negative electrode includes a second negative electrode current collector, a second negative electrode active material layer, and an interlayer disposed between the second negative electrode current collector and the second negative electrode active material layer, the second negative electrode current collector includes a first surface and a second surface, the first surface facing the inner layer, and the second surface being an opposite surface to the first surface; the second negative electrode active material layer is disposed on the first surface and is not disposed on the second surface, The thickness of the second negative electrode current collector is thinner than the thickness of the first negative electrode current collector, the second negative electrode active material layer is thicker than the first negative electrode active material layer.

20. dry mixing a second positive electrode active material, a dry conductive material, and a dry binder to form a dry mixture; providing a second positive electrode current collector; disposing an intermediate layer on one surface of a second positive electrode current collector; and disposing the dry mixture on the intermediate layer and rolling the mixture to fabricate a second positive electrode having a second positive electrode active material layer disposed on one surface of the second positive electrode current collector; The lithium battery includes an electrode group stack in which a plurality of positive electrodes and one or more negative electrodes are alternately stacked in a thickness direction, the plurality of positive electrodes includes a first positive electrode and a second positive electrode, The first positive electrode is an inner layer of the electrode group laminate, the second positive electrode is an outermost layer of the electrode group stack, the first positive electrode includes a first positive electrode current collector and a first positive electrode active material layer, the first positive electrode active material layer being disposed on both sides of the first positive electrode current collector; the second positive electrode includes a second positive electrode current collector, a second positive electrode active material layer, and an interlayer disposed between the second positive electrode current collector and the second positive electrode active material layer; the second positive electrode current collector includes a first surface and a second surface, the first surface facing the inner layer, and the second surface being an opposite surface to the first surface; the second positive electrode active material layer is disposed on the first surface and is not disposed on the second surface, The thickness of the second positive electrode current collector is thinner than the thickness of the first positive electrode current collector, the second positive electrode active material layer is thicker than the first positive electrode active material layer.

21. preparing a slurry by mixing a first positive electrode active material, a conductive material, a binder, and a process solvent; providing a first positive electrode current collector; 21. The method of claim 20, further comprising: disposing the slurry on both sides of the first positive electrode current collector and rolling the slurry to fabricate a first positive electrode having first positive electrode active material layers disposed on both sides of the first positive electrode current collector.

Citation Information

Patent Citations

  • Secondary battery

    JP2010232011A

  • Electrode, lithium battery including the same, and electrode manufacturing method

    JP2022104913A

  • Lithium ion secondary battery

    WO2019044839A1